2011
DOI: 10.1159/000333212
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Non-B Non-C Hepatocellular Carcinoma: A Single-Center Retrospective Study

Abstract: Background/Aims: To clarify risk factors and clinical features of both hepatitis B surface antigen and anti-HCV negative hepatocellular carcinoma (NBNC-HCC). Methods: HCC patients (n = 1,109) diagnosed at a single center were categorized based on the presence of serum hepatitis B surface antigen and HCVAb. Clinical characteristics of 127 NBNC-HCC patients were evaluated. Results: NBNC-HCC patients were stratified as those with alcoholic liver disease (ALD-HCC, n = 42) and alcohol-unrelated liver disease (non-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…The analysis of the characteristics of NBNC HCC indicated that the mean age, rate of complications associated with diabetes and BMI were significantly higher in these cases compared with cases of virus-related HCC, in agreement with previous reports (5)(6)(7)(8)(9)(10)(11)(12). Patients with NBNC HCC exhibited a good liver function, although a number of patients presented with a large tumor size (6), possibly as they were not examined periodically due to the absence of hepatitis virus infection.…”
Section: Discussionsupporting
confidence: 90%
“…The analysis of the characteristics of NBNC HCC indicated that the mean age, rate of complications associated with diabetes and BMI were significantly higher in these cases compared with cases of virus-related HCC, in agreement with previous reports (5)(6)(7)(8)(9)(10)(11)(12). Patients with NBNC HCC exhibited a good liver function, although a number of patients presented with a large tumor size (6), possibly as they were not examined periodically due to the absence of hepatitis virus infection.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have described the clinicopathological features of NBNC‐HCC that included the contribution of past HBV infection . In these reports, HCC patients of various stages and treatments, such as resection, radiofrequency ablation, and transarterial chemoembolization, were enrolled, so it was difficult to compare outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies on prognostic factors in NBNC-HCC patients identified gender, serum albumin level, DCP, tumor size, tumor capsule, and tumor differentiation as significant independent factors for OS [6, 9, 2931]. Therefore, in terms of OS, preoperative liver functions such as serum albumin and Child-Pugh class are important as patient-related factor and degree of tumor malignancy as tumor-related factor, showing the results similar to those in hepatitis virus-related HCC patients.…”
Section: Discussionmentioning
confidence: 99%